Assessment of dehydration, sweat rate, electrolyte loss through the field sweat test on athletes - Sujin Bae; Park Hyon (Korea Institute of Sport Science, 2020)
Purpose The purpose of this study was to confirm and evaluate the assessment of dehydration, whole body sweat rate, sweat sodium · potassium concentration, and fluid intake during workout in college badminton and rugby athletes using the field sweat test. Methods 14 male badminton athletes and 17 male rugby athletes were measured during an usual training session in a typical environment. USG(urine specific gravity) was measured before the start of training. Whole body sweat rate, sweat sodium·potassium concentration, and fluid intake were measured during and post a session of training. Results USG higher than 1.023 in both groups, which was considered as dehydrated. Sweating rate were 1.037±0.315L/h for the badminton athletes and 1.987±0.386L/h for the rugby athletes. The concentration of sodium and potassium were 53.6±20.2mmol/L, 4.1±0.7mmol/L for badminton athletes, and 55.6±15.2mmol/L, 4.3±0.5mmol/L for rugby athletes, respectively. The loss of sodium and potassium were 1.02±0.48g, 0.08±0.02g for badminton athletes, and 1.95±0.52g, 0.15±0.03g for rugby athletes, respectively. Conclusions In this study, a standard protocol of field sweat test was suggested as a useful factor in evaluating athletes' hydration status and electrolyte loss during a routine in-door or out-door training session. And, it is expected to build reliable data to establish a standard hydration guideline for Korean athletes.